The Concept of Love in Ibn Sina's Philosophical Mysticism: A Synthesis of Rationality and Sufism - Ramdani, Dani; Bakhtiar, Amsal (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2024)
This article discusses Ibn Sina’s concept of love. Through this concept, the researcher wants to show that Ibn Sina's thought is not only identical to empirical, logical, and rational peripatetic philosophy, but also Sufistic. This study employed a qualitative method using a philosophical tasawwuf approach. The results show that everything that exists – whether animate or not – contains the energy of love in itself. Essentially, love is a manifestation of Allah, The Essence, who has qualities of Absolute Goodness and Perfection. In this case, God is The Subject of Love. Second, God as Absolute Goodness and Perfection is The Object of Love–the final destination movement of all that exists. Finally, through true love, people can be connected with their God, occupy the highest position, and achieve true happiness. According to Ibn Sina, humans in this stage are called Arif.